Modernisasi Kurikulum Pendidikan Dayah Pada Ma’had `Aly - hanafiah, muhibuddin muhib (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2023)
A number of major pesantrens (Islamic boarding schools) in Indonesia have already had an Islamic religious education unit at the higher education level, known as Ma’had Aly. According to the PMA No. 71 of 2015, Ma’had Aly refers to an Islamic religious college that organizes academic education in the field of mastery of Islamic religious knowledge (tafaqquh fi al-din) based on the kitab kuning (traditionally religious text books printed in yellow papers) administered by and used within the pesantren environment. Ma’had Aly is an institution established for high-level ulama (Islamic clerical) education as a continuation of diniyah education at the Ulya/Madrasah Aliyah level or equivalent education. The learning system implementated at Ma’had Aly follows the curriculum guidelines as decreed in the Decree of the Director General of Islamic Religious Institutional Development. In the Ma’had Aly curriculum guidelines, the curriculum is described as study plans and learning programs to achieve the quality for professional competency and the quality of academic competencies. The quality standards are predetermined by relevant Ma’had Aly administrator and negotiated with the Majlis Masyaikh. The standard academic quality aims at creating Ma’had Aly graduates to have competences as the ulama who can carry out their functions for community development in counselling, role modelling, educating, and giving religious fatwas in response to global challenges in the future. Ma’had Aly is one of the latest developments in the world of Islamic education in Indonesia.